Gendered resilience in India’s seaweed farming: Highlighting policy lessons from the COVID-19 pandemic for inclusive Blue economy framework - Sundaram Swathi Lekshmi Perumal; Radhakrishnan Kalidoss; Gopal Nikita; D. Divu; Mojjada Suresh Kumar; V.P. Vipin Kumar; George Saju; S. Surya; R. Narayanakumar; Kingsly Jose; V.A. Leslie; S.S. Arabindoo; et al. (Marine Policy, 2026)

Assessment of microplastics contamination in riverine environments: Urban stretch of Cauvery and Kollidam rivers of southern India - S. Venkatramanan; K. Radhakrishnan; R. Muthuramalingam; K. Sivakumar; T. Kongeswaran; K. Prabakaran; R. Rameshkumar; V. Madavaraj (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Template complex synthesis of octadecan-1-amine with 2- benzoylpyridine and Cu2+: structural, anticancer, DPPH, SOD and FRAP studies - S. Vennila; K.S. Nagaraja; L. Lakshmi; V Radhakrishnan (Next Research, 2026)

Models reveal the importance of alternative hosts and environmental transmission for emergence of bacterial disease in muskoxen in the Arctic - Juan S. Vargas Soto; Marina Reyne; McCaide Wooten; Sreejith Radhakrishnan; Fabien Mavrot; Susan Kutz; Taya Forde; Eric R. Morgan (Ecological Modelling, 2026)

Compact disc-based sensor utilizing Er2O3/Co3O4 nanorods anchored on rGO nanosheets for enhanced detection of hydrogen sulfide at room temperature - S. Lokesh Amith; Chelliah Koventhan; Yesurajan Allwin Richard; Kattamuthu Radhakrishnan; Shakkthivel Piraman (Journal of Hazardous Materials, 2026)

Genetic diversity assessment of near-threatened endemic catfish Clarias dussumieri in Western Ghats, India: implications for conservation - Divya Prema Radhakrishnan; Divya Merin Jose; C. P. Abhilash; V. S. Basheer; Uttam Kumar Sarkar (Hydrobiologia, 2026)

Harnessing the synergistic advantages of functional modified (defect generated, Ni and S co-doped) TiO2/NiS S-scheme photocatalyst and halloysite nanotube support for efficient photodegradation of several volatile organics - Dani S. Assi; Vaithinathan Karthikeyan; Padmanaban Radhakrishnan; Venkatramanan Kannan; Rashmi Mannu; Chongkol Sungoum; Vaskuri C.S. Theja; Gopalan Anantha Iyengar; Dong-Eun Lee; Vellaisamy A.L. Roy (Journal of Environmental Chemical Engineering, 2025)

Marine lipids: A review of sources, extraction methods, characterization, and food applications - Rinish Mortin John; Aishwarya Lakshmi Thasvanth Raj; Yuvaraj Dinakarkumar; S. Ivo Romauld; Arokiyaraj Selvaraj; Nadeem Siddiqui; Muthezhilan Radhakrishnan (Food and Humanity, 2025)

Phytomolecule-doped green synthesis of Ag@Fe bimetallic nanocomposites from Abutilon indicum leaf extract: Antimicrobial activity against Mycobacterium spp. and pathogenic bacteria and their cytotoxicity assessment in zebrafish embryos - Mary Shamya Arokiarajan; J. John Christopher; S. Ranjani; S.A. Wasim Akram; K.M. Ramkumar; S. Tirumala Santoshkumar; Noman Anwar; T. Rajaseker; M Radhakrishnan; V. Muzammil Ahmed; Murali Krishna Prasad; K. Kabiruddin Ahmed; et al. (Biocatalysis and Agricultural Biotechnology, 2025)

Diabetic retinopathy: a comprehensive review of pathophysiology and emerging treatments - Mukul Shyam; S. Sidharth; Aleen Veronica; Lakshmipriya Jagannathan; Prathap Srirangan; Vidya Radhakrishnan; Evan Prince Sabina (Molecular Biology Reports, 2025)

A novel nor-megastigmane from the leaves of Rhaphiostylis beninensis - Adeola A. Adegun; Radhakrishnan Srivedavyasasri; Jianping Zhao; Fazila Zulfiqar; Adesegun S. Adeleke; Olukemi A. Odukoya; Ikhlas A. Khan; Zulfiqar Ali (Natural Product Research, 2025)

Optimizing technical efficiency in whiteleg shrimp aquaculture: a double-bootstrap data envelopment analysis - Kalidoss Radhakrishnan; Baban Bayan; Swadesh Prakash; P. S. Ananthan; Anu Susan Sam; Sandip Shil; Arpita Sharma; Srichandan Das; Kota Karuna Sri (Aquaculture International, 2025)

Novel o-Terphenyl Luminophores for Optoelectronic Devices: Synthesis, Photophysical, Electrochemical, and Thermal Analysis - Amarsinh R. Mainak; Pranjali S. Kewate; Vasanti B. Shabade; Vishnu V. Kutwade; Radhakrishnan M. Tigote; Netaji K. Desai; Sidram R. Pujari (Journal of Fluorescence, 2025)

Environmental exposure assessment in the international prospective study of Chronic Kidney Disease of UnceRtain Etiology (CKDu) in Agricultural Communities (CURE) research consortium: Design and protocol development - Marvin González-Quiroz; Anna Aceituno; Shuchi Anand; Alexander van Geen; Lawrence S. Engel; Emmanuel Jarquin; Clemens Ruepert; Nicole Villegas-González; Mariela Arias-Hidalgo; Nora Franceschini; Daylin Anchía-Pastrán; Karla Solano-Diaz; et al. (Science of The Total Environment, 2025)

Microsatellite-Based Genetic Diversity, Population Structure and Bottleneck Analysis in Peanut: Conservation and Utilization Implications - Chandramohan Sangh; Janki BharatBhai Pandya; Vora Zarna; Radhakrishnan T; S. K. Bera (Plant Molecular Biology Reporter, 2025)

Bacillus licheniformis and commercial fungicides exhibit high potential against major pathogens inciting grain discolouration disease in rice, Oryza sativa L. - P. K. Amrith; M. Surendran; N. V. Radhakrishnan; Susha S. Thara; T. Anuradha; B. Ajay (Indian Phytopathology, 2025)

Unveiling Hidden Water Resources: Deep Learning and Remote Sensing for Subsurface Hydrology for Environmental Health - Jampani Satish Babu; Dinesh G.; R. Suganya; P. Radhakrishnan; Anand Sutar; Alex David S.; L. Malleswara Rao (Remote Sensing in Earth Systems Sciences, 2025)

Deep Learning in Analyzing Carbon Flux Patterns for Environmental Health: Remote Sensing Insights for Climate Mitigation Strategies - Hariharan Subramani; M. Neela Harish; Selva kumar S; P. Radhakrishnan; L. N. K. Sai Madupu; Kasturi Sai Sandeep; Divya Nimma (Remote Sensing in Earth Systems Sciences, 2025)

Utilization of Fibre-reinforced plastic material as co-firing effect with Prosopis Juliflora in fluidized bed gasifier - Keerthivasan Kunjupillai Chandrasekaran; Vivekanandan Shanmugam; S. Raju; Gopinath Govindan Radhakrishnan (Bioresource Technology Reports, 2025)

Internet of Things (IoT)- based strain monitoring system for large engineering structures - S. Anjuna; Nisha Radhakrishnan; Greegar George (Innovative Infrastructure Solutions, 2025)

Evaluating urban heat island to achieve sustainable development goals: A case study of Tiruchirappalli city, India - Deepthi S; Sudalaimani K; Radhakrishnan Shanthi Priya; Radhakrishnan S (Sustainable Cities and Society, 2024)

Advancing nutraceuticals in a promising frontier in modern healthcare - Flora Shah; Karuppiah Nagaraj; S. Kamalesu; L. Radhakrishnan; Renuka Venkatachalapathy (Food and Humanity, 2024)

Innovative nanotechnological solutions for sustainable agriculture amidst rising population demands - Flora Shah; Karuppiah Nagaraj; Sanyukta Papriwal; Gargi Selwal; Ruchik Mistry; Prasenjit Maity; S. Kamalesu; L. Radhakrishnan; Renuka Venkatachalapathy (Food and Humanity, 2024)

Performance prediction of emulsion treated base layer mixes using indirect tensile strength and resilient modulus test parameters - Jithin Kurian Andrews; Vishnu Radhakrishnan; Reebu Zachariah Koshy; C. S. R. K. Prasad (Innovative Infrastructure Solutions, 2024)

Multiple criteria-based sensor optimization for Structural Health Monitoring of civil engineering structures - Anjuna S.; Nisha Radhakrishnan; Greegar George (Innovative Infrastructure Solutions, 2024)

Energy efficiency and economics of small-scale fisheries (SSF) in India: A VIKOR based multicriteria decision-making model for sustainable fisheries management - Swathi Lekshmi Perumal Sundaram; Kalidoss Radhakrishnan; R. Narayanakumar; Vipin Kumar V. P; S. Surya; D. Divu; Nikita Gopal; Jose Kingsly; V.A. Leslie; Suresh Kumar Mojjada; Mayur Shivdas Tade; Aarsha Subramanian; et al. (Journal of Cleaner Production, 2024)

Water budgeting for production of hatchlings, fry and fingerlings of Asian catfish, Clarias magur - S. Ferosekhan; P. Velmurugan; K. Radhakrishnan; S.P. Kamble; M.K. Bairwa; S.K. Sahoo; P.C. Das (Aquaculture, 2024)

A Histone H2A Derived Antimicrobial Peptide from the Blue Swimmer Crab, Portunus pelagicus Linnaeus 1758: In silico Characterization and Phylogenetic Analysis - V. V. Anooja; P. P. Athira; Kesavan Dhanya; S. Neelima; M. V. Anju; K. Archana; S. Muhammed Musthafa; C. K. Radhakrishnan; Rosamma Philip (Thalassas: An International Journal of Marine Sciences, 2024)

Pixel Reduction of High-Resolution Image Using Principal Component Analysis - Ramachandran Radhakrishnan; Manimegalai Thirunavukkarasu; R. Thandaiah Prabu; G. Ramkumar; S. Saravanakumar; Anitha Gopalan; V. Rama Lahari; B. Anusha; Shaik Hasane Ahammad; Ahmed Nabih Zaki Rashed; Md. Amzad Hossain (Journal of the Indian Society of Remote Sensing, 2024)

Unravelling the Parkinson’s puzzle, from medications and surgery to stem cells and genes: a comprehensive review of current and future management strategies - Krishnapriya Chandrababu; Vineeth Radhakrishnan; A. S. Anjana; Rahul Rajan; Unnikrishnan Sivan; Syam Krishnan; P. S. Baby Chakrapani (Experimental Brain Research, 2024)

Diversity of complex polysaccharide degrading bacteria from the sediments of interlinked high Arctic fjords, Svalbard - Vishnupriya S.; Jabir T.; Adarsh B.M.; Hafsa Kattatheyil; Shahana Kabeer S.; Krishnan K.P.; Radhakrishnan C.K.; Mohamed Hatha A.A. (Regional Studies in Marine Science, 2023)

A critical review on pyrolysis method as sustainable conversion of waste plastics into fuels - K. Radhakrishnan; P. Senthil Kumar; Gayathri Rangasamy; L. Praveen Perumal; S. Sanaulla; S. Nilavendhan; V. Manivasagan; K. Saranya (Fuel, 2023)

Measurement and comparison of photosynthetically active radiation by different methods at Delhi - Humaira Ghayas; S. R. Radhakrishnan; Vinay Kumar Sehgal; Sachchidanand Singh (Theoretical and Applied Climatology, 2022)

Relative abundance of PGRs in the liquid endosperm of young nuts of Cocos nucifera L. parental cultivars and their reciprocal hybrids - V. V. Amritha; K. G. Ajith Kumar; Parvathy S. Nair; N. V. Radhakrishnan; K. Prathapan; B. N. Bessy Raj (Plant Physiology Reports, 2022)

Pharmaceutical perspective of neuropathic pain management for primary care providers - Sandhya Jinesh; Justin Kullgren; Gollapudi S. Shankar; Rajan Radhakrishnan (Inflammopharmacology, 2022)

Study of variation of aerosol optical properties over a high altitude station in Indian Western Himalayan region, palampur using raman lidar system - Shishir Kumar Singh; S. R. Radhakrishnan; Jaswant; Sumit Kumar Mishra; Devesh Kumar Shukla; Ashish Ranjan; Chhemendra Sharma (Journal of Atmospheric Chemistry, 2022)

Non-thermal technologies: Solution for hazardous pesticides reduction in fruits and vegetables - Ranjitha Gracy T. K.; Sharanyakanth P. S.; Mahendran Radhakrishnan (Critical Reviews in Food Science and Nutrition, 2022)

Correction to: Alginate-liposomal construct for bupivacaine delivery and MSC function regulation - Mollie S. Davis; Ileana Marrero-Berrios; Isabel Perez; Timothy Maguire; Palangat Radhakrishnan; Devasena Manchikalapati; Joseph SchianodiCola; Hattiyangangadi Kamath; Rene S. Schloss; Joel Yarmush (Drug Delivery and Translational Research, 2022)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Anti-inflammatory effect and mechanism of action of ellagic acid-3,3′,4-trimethoxy-4′- O -α-L-rhamnopyranoside isolated from Hopea parviflora in lipopolysaccharide-stimulated RAW 264.7 macrophages - B. Prabha; S. Sini; T. S. Priyadarshini; P. Sasikumar; Greeshma Gopalan; Jayesh P. Joseph; M. M. Jithin; V. V. Sivan; P. Jayamurthy; K. V. Radhakrishnan (Natural Product Research, 2021)

Protective effect of (+)–catechin against lipopolysaccharide-induced inflammatory response in RAW 264.7 cells through downregulation of NF-κB and p38 MAPK - M. A. Sunil; V. S. Sunitha; Prasanthkumar Santhakumaran; Mohind C. Mohan; Midhun Sebastian Jose; E. K. Radhakrishnan; Jyothis Mathew (Inflammopharmacology, 2021)

Evaluation of various image transformation techniques for the delineation of coastal sand dune features in Tamil Nadu, South India - Praveenraj Durai; Nisha P. Radhakrishnan; K. J. Sarunjith; Aparna S. Bhaskar (Earth Science Informatics, 2021)

Promalabaricone B from Myristica fatua Houtt. seeds demonstrate antidiabetic potential by modulating glucose uptake via the upregulation of AMPK in L6 myotubes - B. Prabha; S. Sini; D. R. Sherin; S. Neethu; K. B. Rameshkumar; T. K. Manojkumar; P. Jayamurthy; K. V. Radhakrishnan (Natural Product Research, 2021)

Fatty acid desaturase-2 (ahFAD2) mutant alleles in peanut (Arachis hypogaea L.) pre-breeding lines: an insight into the source, features, discourse, and selection of novel pre-breeding lines - J. H. Kamdar; M. D. Jasani; B. C. Ajay; Kirti Rani; N. Manivannan; R. P. Vasanthi; K. L. Dobariya; M. K. Pandey; P. Janila; T. Radhakrishnan; R. K. Varshney; S. K. Bera (Genetic Resources and Crop Evolution, 2021)

Hemodynamics mediated epigenetic regulators in the pathogenesis of vascular diseases - C. L. Karthika; S. Ahalya; N. Radhakrishnan; C. C. Kartha; S. Sumi (Molecular and Cellular Biochemistry, 2021)

Inhibition of transient receptor potential vanilloid 1 (TRPV1) channel regulates chikungunya virus infection in macrophages - P. Sanjai Kumar; Tapas K. Nayak; Chandan Mahish; Subhransu S. Sahoo; Anukrishna Radhakrishnan; Saikat De; Ankita Datey; Ram P. Sahu; Chandan Goswami; Soma Chattopadhyay; Subhasis Chattopadhyay (Archives of Virology, 2021)

Water deficit-induced oxidative stress and differential response in antioxidant enzymes of tolerant and susceptible tea cultivars under field condition - M. Nalina; S. Saroja; M. Chakravarthi; R. Rajkumar; B. Radhakrishnan; K. N. Chandrashekara (Acta Physiologiae Plantarum, 2021)

Combined Effect of Pseudomonas spp. Consortium and Fertilizer with Micronutrients on Enhanced yield of Amaranthus tricolor (L.) - S. Soumya; S. Sreejith; K. Shibil Shad; P. Anusha; B. Swathy; R. Renikrishna; S. Saranya; P. Jishma; E. K. Radhakrishnan; A. Remakanthan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2020)

Genome-based trait prediction in multi- environment breeding trials in groundnut - Manish K. Pandey; Sunil Chaudhari; Diego Jarquin; Pasupuleti Janila; Jose Crossa; Sudam C. Patil; Subramaniam Sundravadana; Dhirendra Khare; Ramesh S. Bhat; Thankappan Radhakrishnan; John M. Hickey; Rajeev K. Varshney (Theoretical and Applied Genetics, 2020)
Key message Comparative assessment identified naïve interaction model, and naïve and informed interaction GS models suitable for achieving higher prediction accuracy in groundnut keeping in mind the high genotype × environment interaction for complex traits. Abstract Genomic selection (GS) can be an efficient and cost-effective breeding approach which captures both small- and large-effect genetic factors and therefore promises to achieve higher genetic gains for complex traits such as yield and oil content in groundnut. A training population was constituted with 340 elite lines followed by genotyping with 58 K ‘Axiom_Arachis’ SNP array and phenotyping for key agronomic traits at three locations in India. Four GS models were tested using three different random cross-validation schemes (CV0, CV1 and CV2). These models are: (1) model 1 (M1 = E + L) which includes the main effects of environment (E) and line (L); (2) model 2 (M2 = E + L + G) which includes the main effects of markers (G) in addition to E and L; (3) model 3 (M3 = E + L + G + GE), a naïve interaction model; and (4) model 4 (E + L + G + LE + GE), a naïve and informed interaction model. Prediction accuracy estimated for four models indicated clear advantage of the inclusion of marker information which was reflected in better prediction accuracy achieved with models M2, M3 and M4 as compared to M1 model. High prediction accuracies (> 0.600) were observed for days to 50% flowering, days to maturity, hundred seed weight, oleic acid, rust@90 days, rust@105 days and late leaf spot@90 days, while medium prediction accuracies (0.400–0.600) were obtained for pods/plant, shelling %, and total yield/plant. Assessment of comparative prediction accuracy for different GS models to perform selection for untested genotypes, and unobserved and unevaluated environments provided greater insights on potential application of GS breeding in groundnut.

Data-Driven, Multi-Model Workflow Suggests Strong Influence from Hurricanes on the Generation of Turbidity Currents in the Gulf of Mexico - Courtney Harris; Jaia Syvitski; H.G. Arango; E.H. Meiburg; Sagy Cohen; C.J. Jenkins; Justin Birchler; E.W.H. Hutton; T.A. Kniskern; S. Radhakrishnan; Guillermo Auad (Journal of Marine Science and Engineering, 2020)
Turbidity currents deliver sediment rapidly from the continental shelf to the slope and beyond; and can be triggered by processes such as shelf resuspension during oceanic storms; mass failure of slope deposits due to sediment- and wave-pressure loadings; and localized events that grow into sustained currents via self-amplifying ignition. Because these operate over multiple spatial and temporal scales, ranging from the eddy-scale to continental-scale; coupled numerical models that represent the full transport pathway have proved elusive though individual models have been developed to describe each of these processes. Toward a more holistic tool, a numerical workflow was developed to address pathways for sediment routing from terrestrial and coastal sources, across the continental shelf and ultimately down continental slope canyons of the northern Gulf of Mexico, where offshore infrastructure is susceptible to damage by turbidity currents. Workflow components included: (1) a calibrated simulator for fluvial discharge (Water Balance Model - Sediment; WBMsed); (2) domain grids for seabed sediment textures (dbSEABED); bathymetry, and channelization; (3) a simulator for ocean dynamics and resuspension (the Regional Ocean Modeling System; ROMS); (4) A simulator (HurriSlip) of seafloor failure and flow ignition; and (5) A Reynolds-averaged Navier–Stokes (RANS) turbidity current model (TURBINS). Model simulations explored physical oceanic conditions that might generate turbidity currents, and allowed the workflow to be tested for a year that included two hurricanes. Results showed that extreme storms were especially effective at delivering sediment from coastal source areas to the deep sea, at timescales that ranged from individual wave events (~hours), to the settling lag of fine sediment (~days).

G × E interactions in QTL introgression lines of Spanish-type groundnut (Arachis hypogaea L.) - A. L. Rathnakumar; Surendra S. Manohar; Hajisaheb L. Nadaf; Sudam C. Patil; Milind P. Deshmukh; P. P. Thirumalaisamy; Narendra Kumar; H. B. Lalwani; P. Nagaraju; Basavaraj Yenagi; S. S. Patil; J. Suryawanshi; et al. (Euphytica, 2020)

Translational genomics for achieving higher genetic gains in groundnut - Manish K. Pandey; Arun K. Pandey; Rakesh Kumar; Chogozie Victor Nwosu; Baozhu Guo; Graeme C. Wright; Ramesh S. Bhat; Xiaoping Chen; Sandip K. Bera; Mei Yuan; Huifang Jiang; Issa Faye; et al. (Theoretical and Applied Genetics, 2020)
Key message Groundnut has entered now in post-genome era enriched with optimum genomic and genetic resources to facilitate faster trait dissection, gene discovery and accelerated genetic improvement for developing climate-smart varieties. Abstract Cultivated groundnut or peanut ( Arachis hypogaea ), an allopolyploid oilseed crop with a large and complex genome, is one of the most nutritious food. This crop is grown in more than 100 countries, and the low productivity has remained the biggest challenge in the semiarid tropics. Recently, the groundnut research community has witnessed fast progress and achieved several key milestones in genomics research including genome sequence assemblies of wild diploid progenitors, wild tetraploid and both the subspecies of cultivated tetraploids, resequencing of diverse germplasm lines, genome-wide transcriptome atlas and cost-effective high and low-density genotyping assays. These genomic resources have enabled high-resolution trait mapping by using germplasm diversity panels and multi-parent genetic populations leading to precise gene discovery and diagnostic marker development. Furthermore, development and deployment of diagnostic markers have facilitated screening early generation populations as well as marker-assisted backcrossing breeding leading to development and commercialization of some molecular breeding products in groundnut. Several new genomics applications/technologies such as genomic selection, speed breeding, mid-density genotyping assay and genome editing are in pipeline. The integration of these new technologies hold great promise for developing climate-smart, high yielding and more nutritious groundnut varieties in the post-genome era.

Correction to: Common Methodology for Cardiac and Ocular Artifact Suppression from EEG Recordings by Combining Ensemble Empirical Mode Decomposition with Regression Approach - Rajesh Patel; K. Gireesan; S. Sengottuvel; M. P. Janawadkar; T. S. Radhakrishnan (Journal of Medical and Biological Engineering, 2020)

Distribution of multi-virulence factors among Aeromonas spp. isolated from diseased Xiphophorus hellerii - Soumya Das; R. Aswani; B. Jasim; K. S. Sebastian; E. K. Radhakrishnan; Jyothis Mathew (Aquaculture International, 2020)

Role of flavonoids in thrombotic, cardiovascular, and inflammatory diseases - Cijo George Vazhappilly; Shabbir Ahmed Ansari; Rula Al-Jaleeli; Aya Mudhafar Al-Azawi; Wafaa S. Ramadan; Varsha Menon; Rawad Hodeify; Shoib Sarwar Siddiqui; Maxime Merheb; Rachel Matar; Rajan Radhakrishnan (Inflammopharmacology, 2019)

Epigenetic Modifier Based Enhancement of Piperine Production in Endophytic Diaporthe sp. PF20 - B. Jasim; Neethu Sahadevan; S. Chithra; Jyothis Mathew; E. K. Radhakrishnan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2019)

Beneficial Changes in Capsicum frutescens Due to Priming by Plant Probiotic Burkholderia spp. - Rohini Sabu; R. Aswani; K. S. Nidheesh; J.G. Ray; A. Remakanthan; E. K. Radhakrishnan (Probiotics and Antimicrobial Proteins, 2019)

Genotyping-by-sequencing based genetic mapping reveals large number of epistatic interactions for stem rot resistance in groundnut - Sneha M. Dodia; Binal Joshi; Sunil S. Gangurde; Polavakkalipalayam P. Thirumalaisamy; Gyan P. Mishra; Dayama Narandrakumar; Pooja Soni; Arulthambi L. Rathnakumar; Jentilal R. Dobaria; Chandramohan Sangh; Annapurna Chitikineni; Sumitra V. Chanda; et al. (Theoretical and Applied Genetics, 2019)

Accumulation of Heavy Metals in Some Marine Fisheries Resources Collected from Gulf of Mannar Marine Biosphere Reserve, Southeast Coast of India - S. Rameshkumar; P. Prabhakaran; K. Radhakrishnan; R. Rajaram (Proceedings of the Zoological Society, 2018)

Dietary Supplement of Medicinal Herbal Leaf Powder on Growth Performance, Digestive Enzymes Activities, Energy Utilization and Vitamin Levels of the Freshwater Prawn Macrobrachium rosenbergii - T. Muralisankar; P. Saravana Bhavan; S. Radhakrishnan; P. Santhanam (Proceedings of the Zoological Society, 2018)

Design of novel amyloid β aggregation inhibitors using QSAR, pharmacophore modeling, molecular docking and ADME prediction - Lilly Aswathy; Radhakrishnan S. Jisha; Vijay H. Masand; Jayant M. Gajbhiye; Indira G. Shibi (In Silico Pharmacology, 2018)

Alginate-liposomal construct for bupivacaine delivery and MSC function regulation - Mollie S. Davis; Ileana Marrero-Berrios; Isabel Perez; Timothy Maguire; Palangat Radhakrishnan; Devasena Manchikalapati; Joseph SchianodiCola; Hattiyangangadi Kamath; Rene S. Schloss; Joel Yarmush (Drug Delivery and Translational Research, 2018)

New tetranorlabdanoic acid from aerial parts of Salvia aethiopis - Radhakrishnan Srivedavyasasri; Miriah B. White; Tatyana S. Kustova; Nadezhda G. Gemejiyeva; Charles L. Cantrell; Samir A. Ross (Natural Product Research, 2018)

DNAzyme Based Amplified Biosensor on Ultrasensitive Fluorescence Detection of Pb (II) Ions from Aqueous System - A. Ravikumar; P. Panneerselvam; K. Radhakrishnan; Norhashimah Morad; C. D. Anuradha; S. Sivanesan (Journal of Fluorescence, 2017)

Exploration of 3,6-dihydroimidazo(4,5-d)pyrrolo(2,3-b)pyridin-2(1H)-one derivatives as JAK inhibitors using various in silico techniques - Radhakrishnan S. Jisha; Lilly Aswathy; Vijay H. Masand; Jayant M. Gajbhiye; Indira G. Shibi (In Silico Pharmacology, 2017)

Suppression of Baseline Wander Artifact in Magnetocardiogram Using Breathing Sensor - Rajesh Patel; K. Gireesan; S. Sengottuvel; M. P. Janawadkar; T. S. Radhakrishnan (Journal of Medical and Biological Engineering, 2017)

Common Methodology for Cardiac and Ocular Artifact Suppression from EEG Recordings by Combining Ensemble Empirical Mode Decomposition with Regression Approach - Rajesh Patel; K. Gireesan; S. Sengottuvel; M. P. Janawadkar; T. S. Radhakrishnan (Journal of Medical and Biological Engineering, 2017)
Electroencephalography (EEG) is a non-invasive way of recording brain activities, making it useful for diagnosing various neurological disorders. However, artifact signals associated with eye blinks or the heart spread across the scalp, contaminating EEG recordings and making EEG data analysis difficult. To solve this problem, we implement a common methodology to suppress both cardiac and ocular artifact signal, by correlating the measured contaminated EEG signals with the clean reference electro-oculography (EOG) and electrocardiography (EKG) data and subtracting the scaled EOG and EKG from the contaminated EEG recording. In the proposed methodology, the clean EOG and EKG signals are extracted by subjecting the raw reference time-series data to ensemble empirical mode decomposition to obtain the intrinsic mode functions. Then, an unsupervised technique is used to capture the artifact components. We compare the distortion introduced into the brain signal after artifact suppression using the proposed method with those obtained using conventional regression alone and with a wavelet-based approach. The results show that the proposed method outperforms the other techniques, with an additional advantage of being a common methodology for the suppression of two types of artifact.

Spectral and Lensing Characteristics of Gel-Derived Strontium Tartrate Single Crystals Using Dual-Beam Thermal Lens Technique - I. Rejeena; V. Thomas; S. Mathew; B. Lillibai; V. P. N. Nampoori; P. Radhakrishnan (Journal of Fluorescence, 2016)

Effects of Probiotics on Survival, Growth and Digestive Enzymes Activities in Freshwater Prawn Macrobrachium rosenbergii (De Man 1879) - C. Seenivasan; S. Radhakrishnan; T. Muralisankar; P. Saravana Bhavan (Proceedings of the Zoological Society, 2016)

Upper Airway Elasticity Estimation in Pediatric Down Syndrome Sleep Apnea Patients Using Collapsible Tube Theory - Dhananjay Radhakrishnan Subramaniam; Goutham Mylavarapu; Keith McConnell; Robert J. Fleck; Sally R. Shott; Raouf S. Amin; Ephraim J. Gutmark (Annals of Biomedical Engineering, 2016)

Compliance Measurements of the Upper Airway in Pediatric Down Syndrome Sleep Apnea Patients - Dhananjay Radhakrishnan Subramaniam; Goutham Mylavarapu; Keith McConnell; Robert J. Fleck; Sally R. Shott; Raouf S. Amin; Ephraim J. Gutmark (Annals of Biomedical Engineering, 2016)

Population genetic structure of the shovel-nosed lobster Thenus unimaculatus (Decapoda, Scyllaridae) in Indian waters based on RAPD and mitochondrial gene sequences - N. S. Jeena; A. Gopalakrishnan; J. K. Kizhakudan; E. V. Radhakrishnan; Raj Kumar; P. K. Asokan (Hydrobiologia, 2016)

Enhanced anti-fibrogenic effects of novel oridonin derivative CYD0692 in hepatic stellate cells - Fredrick J. Bohanon; Xiaofu Wang; Brittany M. Graham; Anesh Prasai; Sadhashiva J. Vasudevan; Chunyong Ding; Ye Ding; Geetha L. Radhakrishnan; Cristiana Rastellini; Jia Zhou; Ravi S. Radhakrishnan (Molecular and Cellular Biochemistry, 2015)

Genotype–phenotype analysis of von Hippel–Lindau syndrome in fifteen Indian families - Narendranath Vikkath; Sindhu Valiyaveedan; Sheela Nampoothiri; Natasha Radhakrishnan; Gopal S. Pillai; Vasantha Nair; Ginil Kumar Pooleri; Georgie Mathew; Krishnakumar N. Menon; Prasanth S. Ariyannur; Ashok B. Pillai (Familial Cancer, 2015)

Influence of Probiotics on Survival, Growth, Biochemical Changes and Energy Utilization Performance of Macrobrachium rosenbergii Post-larvae - C. Seenivasan; S. Radhakrishnan; R. Shanthi; T. Muralisankar; P. Saravana Bhavan (Proceedings of the Zoological Society, 2015)

Marker-assisted introgression of a QTL region to improve rust resistance in three elite and popular varieties of peanut (Arachis hypogaea L.) - Rajeev K. Varshney; Manish K. Pandey; Pasupuleti Janila; Shyam N. Nigam; Harikishan Sudini; M. V. C. Gowda; Manda Sriswathi; T. Radhakrishnan; Surendra S. Manohar; Patne Nagesh (Theoretical and Applied Genetics, 2014)

Influence of medicinal herbs (Alteranthera sessilis, Eclipta alba and Cissus quadrangularis) on growth and biochemical parameters of the freshwater prawn Macrobrachium rosenbergii - S. Radhakrishnan; P. Saravana Bhavan; C. Seenivasan; R. Shanthi; R. Poongodi (Aquaculture International, 2014)

UV-Visible Photoluminescence of TiO2 Nanoparticles Prepared by Hydrothermal Method - S. Mathew; Amit kumar Prasad; Thomas Benoy; P. P. Rakesh; Misha Hari; T. M Libish; P. Radhakrishnan; V. P. N. Nampoori; C. P. G. Vallabhan (Journal of Fluorescence, 2012)

Mathematical Simulation of Membrane Protein Clustering for Efficient Signal Transduction - Krishnan Radhakrishnan; Ádám Halász; Meghan M. McCabe; Jeremy S. Edwards; Bridget S. Wilson (Annals of Biomedical Engineering, 2012)

Identification of hot spots and well managed areas of Pichavaram mangrove using Landsat TM and Resourcesat—1 LISS IV: an example of coastal resource conservation along Tamil Nadu Coast, India - T. Srinivasa Kumar; R. S. Mahendra; Shailesh Nayak; K. Radhakrishnan; Kali C. Sahu (Journal of Coastal Conservation, 2012)

Shifting of Fluorescence Peak in CdS Nanoparticles by Excitation Wavelength Change - S. Mathew; Santhi Ani Joseph; P. Radhakrishnan; V. P. N. Nampoori; C. P. G. Vallabhan (Journal of Fluorescence, 2011)

Identification of several small main-effect QTLs and a large number of epistatic QTLs for drought tolerance related traits in groundnut (Arachis hypogaea L.) - K. Ravi; V. Vadez; S. Isobe; R. R. Mir; Y. Guo; S. N. Nigam; M. V. C. Gowda; T. Radhakrishnan; D. J. Bertioli; S. J. Knapp; R. K. Varshney (Theoretical and Applied Genetics, 2011)

Spatial learning-induced egr-1 expression in telencephalon of gold fish Carassius auratus - K. Emmanuvel Rajan; A. Ganesh; S. Dharaneedharan; K. Radhakrishnan (Fish Physiology and Biochemistry, 2011)

Thermodynamics of chromium(III) adsorption onto a cation exchanger derived from saw dust of Jack wood - T. S. Anirudhan; P. G. Radhakrishnan (Environmental Chemistry Letters, 2011)

Diversity-oriented, one-pot, multi-component synthesis of substituted uracil derivatives - Yogesh Y. Pedgaonkar; Mariam S. Degani; Radhakrishnan P. Iyer (Molecular Diversity, 2011)

A locus for juvenile myoclonic epilepsy maps to 2q33–q36 - Rinki Ratnapriya; Joseph Vijai; Jayaram S. Kadandale; Rajesh S. Iyer; Kurupath Radhakrishnan; Anuranjan Anand (Human Genetics, 2010)

Preliminary screening for antibacterial and antimycobacterial activity of actinomycetes from less explored ecosystems - Manikkam Radhakrishnan; S. Suganya; Ramasamy Balagurunathan; Vanaja Kumar (World Journal of Microbiology and Biotechnology, 2010)

Mulberry biodiversity conservation through cryopreservation - Ananda Rao Atmakuri; Rekha Chaudhury; S. K. Malik; Suseel Kumar; Radhakrishnan Ramachandran; S. M. H. Qadri (In Vitro Cellular & Developmental Biology - Plant, 2009)

Development and characterisation of a novel animal model of prostate inflammation-induced chronic pelvic pain - R. Radhakrishnan; R. S. Nallu (Inflammopharmacology, 2009)

Brain tissue phantoms for optical near infrared imaging - K. Prahlad Rao; S. Radhakrishnan; M. Ramasubba Reddy (Experimental Brain Research, 2006)

Identification of an atypical form of 30 kDa SOD—a possible virulence factor in clinical isolates of Shigella spp. - Radhakrishnan Prakash; Halagowder Devaraj; S. Niranjali Devaraj (Molecular and Cellular Biochemistry, 2004)

Three-dimensional stress analysis for the mechanics of plantar ulcers in diabetic neuropathy - V. J. Thomas; K. M. Patil; S. Radhakrishnan (Medical & Biological Engineering & Computing, 2004)

Agnoprotein and its coding sequences play regulatory roles in JC virus gene transcription and replication in glial cells - M Safak; R Biffi; S Radhakrishnan; S Woolridge; I K Sariyer; I Akan; J Gordon; S Amini; P Ferrante; K Khalili (Journal of NeuroVirology, 2004)

Genetic association analysis of KCNQ3 and juvenile myoclonic epilepsy in a South Indian population - J. Vijai; A. Kapoor; H. M. Ravishankar; P. J. Cherian; A. S. Girija; B. Rajendran; G. Rangan; S. Jayalakshmi; S. Mohandas; K. Radhakrishnan; A. Anand (Human Genetics, 2003)

Real-time automatic extraction of lumen region and boundary from endoscopic images - S. Kumar; K. V. Asari; D. Radhakrishnan (Medical & Biological Engineering & Computing, 1999)

Technique of distortion correction in endoscopic images using a polynomial expansion - K. V. Asari; S. Kumar; D. Radhakrishnan (Medical & Biological Engineering & Computing, 1999)